2013
DOI: 10.1016/j.jce.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Legal centralization and the birth of the secular state

Abstract: This paper investigates the relationship between the historical process of legal centralization and increased religious toleration by the state. We develop a model in which legal centralization leads to the criminalization of the religious beliefs of a large proportion of the population. This process initially leads to increased persecution, but, because these persecutions are costly, it eventually causes the state to broaden the standards of orthodox belief and move toward religious toleration. We compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 60 publications
2
9
0
Order By: Relevance
“…45 But the empirical evidence we present suggests that the new nation states of western Europe were less responsive to it. This is consistent with the findings that stronger states were responsible for ending the European witch-hunts in the late seventeenth century (Levack, 1996;Johnson and Koyama, 2011) and with the argument that the rise of larger and more centralized states led to a gradual increase in bounds of religious toleration in the early modern period (Johnson and Koyama, 2012a). 44 For studies of the expulsion of Jews from England see Leonard (1891); Elman (1937);Ovrut (1977); Menache (1987); Stacey (1997Stacey ( , 2000; Mundill (1998);Katznelson (2005); Koyama (2010b).…”
Section: Why Did the Relationship Between Weather And Expulsions Breasupporting
confidence: 90%
See 1 more Smart Citation
“…45 But the empirical evidence we present suggests that the new nation states of western Europe were less responsive to it. This is consistent with the findings that stronger states were responsible for ending the European witch-hunts in the late seventeenth century (Levack, 1996;Johnson and Koyama, 2011) and with the argument that the rise of larger and more centralized states led to a gradual increase in bounds of religious toleration in the early modern period (Johnson and Koyama, 2012a). 44 For studies of the expulsion of Jews from England see Leonard (1891); Elman (1937);Ovrut (1977); Menache (1987); Stacey (1997Stacey ( , 2000; Mundill (1998);Katznelson (2005); Koyama (2010b).…”
Section: Why Did the Relationship Between Weather And Expulsions Breasupporting
confidence: 90%
“…For the effect of this on persecution of minority groups see Johnson and Koyama (2011) and Johnson and Koyama (2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Schmidt (quoted in 2003, 371). 60 See for an overview Zagorin (2003); Johnson and Koyama (2013). As the French Encyclopédie observed that 'the conditions of the sage is very dangerous: there is hardly a nation that is not soiled with the blood of several of those who have professed it' (quoted in Melzer, 2014, 139). rise of the Western Europe and the Great Divergence.…”
Section: The Consequences Of the Literary Inquisitionmentioning
confidence: 99%
“…This suggests that 10 Our analysis of the effects of the literary inquisition is also related to a wider literature on persecutions. Johnson and Koyama (2013) examine the causes of the persecution of heretics in medieval and early modern Europe while Johnson and Koyama (2014) study how legal fragmentation helped perpetuate large-scale witchhunts in seventeenth century France.…”
Section: Introductionmentioning
confidence: 99%
“…We treat t as fixed, but in a fuller model, it presumably would be the rate that drives citizens to their reservation utility (see, for example,Cosgel and Miceli (2009)). 4 InJohnson and Koyama (2013) andCosgel, Miceli, and Rubin (2012), the ruler is able to choose the optimal mix of these two legitimizing inputs. Here we focus on the simple case where he has to choose one or the other.…”
mentioning
confidence: 99%